THE RELATIONSHIP OF 4 (FOUR) GOLD STANDARDS OF NUTRITION TO THE INCIDENT OF STUNTING IN TODDLERS IN TEN VILLAGES OF MONTASIK DISTRICT, ACEH BESAR REGENCY,IN 2020 - Maulida, Hasra; Ariscasari, Putri; Amin, Fauzi Ali (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Stunting is an indicator of failure to grow optimally which is characterized by a height z score (TB) for age below -2 SD. Sustainable Development Goals (SDGs) target the prevalence of stunting in Indonesia to decrease by 19% in 2019-2024. Meanwhile in Indonesia, the prevalence of stunting is still 27.67%, and in ten villages in Montasik District it is also still relatively high at 25%. This research aims to determine the relationship between 4 (four) gold standards of nutrition and the incidence of stunting among toddlers in ten villages in Montasik District, Aceh Besar Regency in 2020. Method: This research uses descriptive analytical method with a cross- sectional design. The population is all toddlers aged 6-59 months in ten villages of Montasik District. Sampling using the Slovin formula resulted 64 toddlers using proportional random sampling techniques. Data analysis used the Chi-Square test with the SPSS-18 application. Results: The results of the study showed that there was a relationship between IMD (p value=0.004), exclusive breastfeeding (p value=0.004), breastfeeding until the age of 2 years (p value=0.037), and birth spacing (p value=0.013) and there was no relationship between breastfeeding practices MP-ASI (p value=0.063), and maternal TB (p value=0.058) with the incidence of stunting in toddlers in ten villages in Montasik District, Aceh Besar Regency in 2020. Recommendation: It is hoped that the Montasik Community Health Center will improve the principles of the 4 (four) gold standards of nutrition for children starting from early initiation of breastfeeding (IMD), exclusive breastfeeding, and MP-ASI until the age of 2 years through counseling at the Posyandu in each village. Midwives are expected to play more active role so that they can provide education to mothers and expectant mothers, therefore they can anticipate childbirth intervals of ≥ 2 years so that child intake can be met to reduce the incidence of stunting.